Exhibiting of tomato breeding characteristics on different types of low-volume technology - A. S. Eroshevskaya (Овощи России)
The comparative test of experimental F1 tomato hybrids was conducted under conditions of two different types of low-volume technology (MPVI "Fitopiramida", technology of growing in mats with drip irrigation) in 2021. The conducted researches have shown that duration of interphase periods, level of yield and fruit quality depend on cultivation technology. According to the data obtained, in conditions of MPVI "Fitopiramida" all studied F1 tomato hybrids enter fruiting faster and provide higher yield compared to the technology of growing in mats, but are inferior in average fruit weight, soluble dry matter content and taste qualities. As perspective F1 tomato hybrids for "Fitopiramida" technology hybrids Ga62(2) and Ga21, submitted for registration to Gossortcommission, were identified. On low-volume technology in mats hybrid Ga27a showed the best result. A strong correlation was found between estimates of the signs "average fruit weight" (r = 0,93) and "soluble dry matter content" (r = 0,81). It is possible to conduct preliminary selections in conditions of low-volume technology in mats according to these signs. For the most reliable assessment and accurate selection of the most perspective tomato hybrids for "Fitopiramida" technology their testing on hydroponic installations is required.